The impact of remission duration on the long-term economic burden of acute myeloid leukemia among patients without hematopoietic stem cell transplant in the United States. (31st December 2022) - Tabah, Ashley; Brady, Brenna L.; Huggar, David; Jariwala-Parikh, Krutika; Huey, Krystal; Copher, Ronda; LeBlanc, Thomas William
Abstract: Background and aims: Acute myeloid leukemia (AML) prognosis is poor, with sustained remission occurring in <35% of young adults and <15% of older adults. This descriptive study examined the potential benefit of prolonged remission on the economic burden of AML. Methods: Using the IBM MarketScan Commercial and Medicare Supplemental databases, we identified newly diagnosed patients with AML without hematopoietic stem cell transplantation from January 1, 2012 to December 31, 2018; AML diagnosis was the index date. Patients had 6 months of pre-index eligibility and were followed until the end of continuous eligibility, study data, or death. Active treatment and supportive care cohorts were defined; duration-of-remission subgroups (0 to <3, 3 to <6, 6 to <12, and ≥12 months) were established among active treatment patients with remission. Healthcare service utilization and costs were reported over follow-up and mutually exclusive treatment, remission, and post-relapse periods. Results: This study included 1, 558 active treatment and 1, 127 supportive care patients who were followed for a median of 232 and 62 days, respectively. Over follow-up, active treatment and supportive care patients incurred mean ± standard deviation all-cause healthcare costs of 55, 723 ± 61, 994 and 68, 596 ± 100, 375 per-patient-per-month (PPPM), respectively. Decreasing PPPM costs were observed with increased remission duration (0 to <3 months: 71, 823 ± 62, 635; 3 to <6 months: 54, 262 ± 44, 734; 6 to <12 months: 35, 287 ± 23, 699; and ≥12 months: 15, 615 ± 10, 560). Although median follow-up varied by up to 5-fold, total costs were largely similar across duration-of-remission subgroups (0 to <3 months: 438, 569 ± 332, 675; 3 to <6 months: 590, 411 ± 598, 245; 6 to <12 months: 482, 902 ± 369, 115; and ≥12 months: 448, 867 ± 316, 133). Conclusions: The economic burden of AML is substantial, even among untreated patients. Further, among patients with remission, longer durations in remission are associated with reduced PPPM healthcare costs, suggesting that remission-prolonging treatments could help mitigate healthcare costs.